2021
DOI: 10.2166/aqua.2021.041
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study on the treatment of lake water with algae by ultrafiltration–ozone–biologically activated carbon

Abstract: For the treatment of lake water with algae, the coagulation–ultrafiltration–ozone–biologically activated carbon (CUF–O3–BAC) integrated process was first used to treat East Taihu Lake water in China, aiming at evaluating the removal efficiencies of algae, permanganate index (CODMn), UV254, NH3-N and disinfection by-products (DBPs) precursors. In addition, the long-term performance of the membrane operation under the fluxes of 60, 70, 80 and 90 L/(m2·h) was also investigated, and kinetic models were established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Different water sources show a range of quality parameters-for example, their pH ranges from 7.1 to 8.7, and they have been treated using various methods like ozonation, ozonation + activated carbon, and ozonation + permanganate. The majority of the investigations were conducted in laboratories; however, some field works [17] have been conducted, too. It has generally been concluded that no ideal ozone dose has been found for algae treatment in all water bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Different water sources show a range of quality parameters-for example, their pH ranges from 7.1 to 8.7, and they have been treated using various methods like ozonation, ozonation + activated carbon, and ozonation + permanganate. The majority of the investigations were conducted in laboratories; however, some field works [17] have been conducted, too. It has generally been concluded that no ideal ozone dose has been found for algae treatment in all water bodies.…”
Section: Introductionmentioning
confidence: 99%